ANALISIS KESALAHAN PENGGUNAAN KATA BANTU 的 [DE] DAN 得 [DÉ] DALAM PEMBELAJARAN BAHASA MANDARIN KELAS XI SMA ISLAM ATHIRAH 1 MAKASSAR - Elmira, Elmira; Usman, Misnawaty; Burhanuddin, Burhanuddin (Universitas Negeri Makassar, 2020)
Abstract. This study aims to classify the types of errors made by students of class X1 SMA Islam Athirah 1 Makassar in the use of的 [de] (belonging/that) and得[dé] (adverb) auxiliary words in Mandarin. The analytical method is used the error analysis method proposed by Ellis in Tarigan (1984). The results of the data analysis showed that there were 170 errors in the students' use of 的 [de] (belonging / that) and 得[dé] (adverb) auxiliary words. There were 111 errors in the use of the的 [de] (belonging / that) auxiliary words (65.29%), which were in the sufficient error category and the error in the use of the得[dé] (adverb) auxiliary word, namely as many as 59 errors (34.71%) which were in the level of error in the category less The error in using the auxiliary的 [de] (belonging / that) which / belongs is in the sufficient with 111 errors (65.29% ). The error in using the auxiliary word 得 [dé] (adverb) is in the less with 59 errors (34.71%).